Die Kirche lehnt nichts von alledem ab, was in diesen Religionen wahr und heilig ist.: zum Verhältnis von christlicher Liturgie und nichtchristlichem Kult - Gäde, Gerhard (Zeitschrift für katholische Theologie, 2000)
This article, in taking the perspective of Vatican Council II in appreciating non-Christian religions, asks how from a Christian point of view, the cult, rite and liturgy of non-Christian religions are to be judged or valued. In other words, is it possible from a Christian point of view to observe in the celebrations of non-Christian religions a means of salvation for their believers? The answer is not only whether the followers or believers of other religions have the possibility of salvation, but, because of the Christian belief in the universal will of God to save all, whether it is possible to understand non-Christian religions as such as ways of salvation. In fact, all religions offer their followers an unsurpassable salvation, which exceeds all human understanding and experience. This character of promise articulates itself in an excellent way in the cultic celebrations of religions. What allows us to distinguish this promise of salvation from mere illusion is the viewing of this promise of salvation from a Christian perspective. This article would like to leave behind a Christian-only exclusiveness or inclusiveness of salvation, in which non-Christian religions are granted only partial truth. In the view of the author, on the one hand, Anglo-American pluralism cannot be an alternative to a Christian-only exclusiveness or inclusiveness of salvation. For, on the other hand, the Christian message itself is an alternative to this either/or view of salvation by the very fact of its relationship with the Sacred Scripture of Israel, thus setting up a paradigm for Christianity's relationship with other religions. The development in the crafting of the Christian message, grounded in the Trinitarian understanding of God, allows as a starting point the ability to proclaim the promise of a universal truth which concedes the promise of salvation offered by other religions. From this Christian perspective, the promise of salvation articulated in non-Christian cults is to be seen as redeeming and therefore to be distinguished from mere illusion.